2022
DOI: 10.1177/20503121221137015
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and associated factors of respectful maternity care in Tirunesh Beijing Hospital, Addis Ababa, Ethiopia, 2021

Abstract: Objective: The main aim of this research was to assess the magnitude of respectful maternity care and associated factors during labour and delivery in Tirunesh Beijing General Hospital, 2021. Methods: Facility-based cross-sectional research was employed among 319 postnatal mothers who were selected by systematic random sampling technique. Bi-variable and multi-variable logistic regression analysis was used to identify associated factors. Variables whose p-value < 0.05 in the multivariable model with 95% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The thematic domains of friendly and abuse‐free care showed that 9% of the respondents felt treated in an unfriendly manner and 15.5% felt verbally abused. A study in Ethiopia using the same validated tool reported a lower incidence of unfriendly care (2.2%) and a higher incidence of verbal abuse (37%) 9 . Another study in Zambia reported 11% for verbal abuse 15 .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The thematic domains of friendly and abuse‐free care showed that 9% of the respondents felt treated in an unfriendly manner and 15.5% felt verbally abused. A study in Ethiopia using the same validated tool reported a lower incidence of unfriendly care (2.2%) and a higher incidence of verbal abuse (37%) 9 . Another study in Zambia reported 11% for verbal abuse 15 .…”
Section: Discussionmentioning
confidence: 96%
“…They were interviewed by trained research assistants with a questionnaire adapted from a screening tool to detect disrespect and abuse during childbirth that was validated in an African population 7 . The adopted screening tool has been validated in some African settings including states within Ethiopia and in Ghana 7,9,10 . Women who declined to provide informed consent were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations